Production of gamma-cyclodextrin by Bacillus cereus cyclodextrin glycosyltransferase using extractive bioconversion in aqueous two-phase system / Lin Yu Kiat - Lin, Yu Kiat (2017)
The first aim of the study was to introduce a practical approach to the recovery of CYCLODEXTRIN GLYCOSYLTRANSFERASE (CGTase) from Bacillus cereus using polyethylene glycol (PEG)/potassium phosphates aqueous two-phase flotation (ATPF) system. The optimal condition for purification of CGTase was attained at 18.0 % (w/w) PEG 8000, 7.0 % (w/w) potassium phosphates, VR of 3.0, 20 % (w/w) crude load at pH 7, and 80 min nitrogen flotation time at a flow rate of 5 L/min. With this optimal condition, purification factor (PFT) of 21.8 and a yield (YT) of 97.1 % were attained. CGTase was successfully purified in a single step using the ATPF. Another aim of the study was on the extractive bioconversion of CGTase using ATPS. Aqueous two-phase system (ATPS) extractive bioconversion provides a platform to integrate bioconversion and purification into a single step process. Thus, the investigation focused on the design of different ATPSs to reduce the steps in bioconversion and purification, thereby increasing the yield and reducing the cost and time of production. Each of the ATPS was evaluated independently. Extractive bioconversion of gamma-cyclodextrin (γ-CD) was evaluated using polyethylene glycol (PEG)/potassium phosphates based ATPS with ATPF-purified CGTase enzyme and soluble starch. The optimum condition was attained in the ATPS constituted of 30.0 % (w/w) PEG 3000 and 7.0 % (w/w) potassium phosphate. A γ-CD concentration of 1.60 mg/mL with a 19 % concentration ratio was recovered after 1 hour bioconversion process. The γ-CD was primarily partitioned to the top phase (YT = 81.88%), with CGTase partitioning in the salt-rich bottom phase (KCGTase= 0.51). Alcohol/salt based ATPS for the extractive bioconversion of γ-CD was studied after the PEG/potassium phosphate-based ATPS experimentation. The effects using alcohols (ethanol, 1-propanol, and 2-propanol) on CGTase bioactivity were investigated. The results showed that the optimum condition for extractive bioconversion of γ-CD was achieved in ATPS of ethanol 24 % (w/w) with potassium phosphates 20 % (w/w) system in the presence of 3.0 % (w/w) sodium chloride (NaCl). The 1 hour extractive bioconversion process recorded a concentration of 0.23 mg/mL of γ-CD harvested. Finally, extractive bioconversion of γ-CD from soluble starch with CGTase enzyme was studied using ethylene oxide-propylene oxide (EOPO)/potassium phosphates ATPS. Different molecular weights of EOPO with potassium phosphates were tested to study their partitioning effect on γ-CD and CGTase. The results showed that the optimum top phase γ-CD yield condition (74.4 %) was achieved in 35.0 % (w/w) EOPO 970 and 10.0 % (w/w) potassium phosphate with 2.0 % (w/w) NaCl. A total of 0.87 mg/mL concentration of γ-CD was produced in EOPO/phosphates ATPS top phase after two hours. The PEG/potassium phosphates ATPS was found to be a better system for extractive bioconversion of γ-CD. The main conclusion of this study was ATPS has a good potential to be applied industrially for the recovery of CGTase and γ-CD production.